Pore multi-fractal characteristics of coal under true triaxial tetrahydrofuran hydraulic injection - Sheng XUE; Feilin HAN; Chunshan ZHENG; Shuaili LIU; Bingjun LIU (Meitan xuebao)
The efficiency of coalbed methane extraction is closely related with multifractal characteristics of pore structures. Clarifying the mechanism of changes in pore structure in coal affected by hydraulic injection has theoretical significance for the solvent-treatment improvement of coal reservoirs. In this study, the true triaxial hydraulic injection and seepage testing experimental platform was adopted to conduct experiments on the injection of tetrahydrofuran (THF) solution and water into coal. Based on low-temperature liquid nitrogen adsorption and mercury intrusion test results, as well as the Barrett-Joyner-Halenda model, Washburn equation and multifractal theory, the changes of heterogeneity and multifractal characteristics of coal pore structure after hydraulic injection were investigated. Meanwhile, the factors influencing pores multifractal parameters variations were discussed. The results indicate that compared to three original coal samples, the total pore volume of coal after water injection increased by 9.98%, 11.92%, and 99.63%, respectively, while the total pore volume after THF injection rose by 37.37%, 27.49%, and 108.35%, respectively. This could be attributed to the synergistic effect of THF injection in fracturing the coal matrix and dissolving small organic molecules within pores, leading to a further enhancement in pore volume expansion. The generalized fractal dimension spectrum and multifractal singularity spectrum of the pore structures in both the original and post-injection coal samples conformed to the laws of multifractal theory, demonstrating that their pore structures possessed multifractal characteristics. Compared to the original coal, the number of pores in coal samples after water and THF injection both increased, with a general increase in the singularity spectrum width Δα (ranging from 0.034 7 to 0.350 5), indicating an enhancement in pore structure heterogeneity. The heterogeneity of micropores in coal samples after THF injection was generally higher than that after water injection, while the heterogeneity of meso-macropores was slightly lower. A positive correlation was observed between the pore volume, specific surface area, and the singularity spectrum width, as well as the low-probability parameter (D–10−D0) of coal samples. Research findings could provide theoretical basis for understanding the heterogeneity of pore structure and changes in local scale properties of coal reservoirs affected by THF hydraulic fracturing, which helps to reveal the pore and permeability improvement characteristics in low-permeability reservoirs.